IDOSOS RESIDENTES EM MORADIA COLETIVA PARA IDOSOS: um espaço de convivência - Leite, Marinês T.; Hildebrandt, Leila M.; Piovesan, Solange M. S.; Renner, Juliana; Renck, João S.; Dietz, Graciele (Salão do Conhecimento, 2013)
Resumo